Implementation of The Teachings of Satya In Shaping The Social Ethics of Hindu Religious Education Students at Iahn Mpu Kuturan - Virgo Agni; Ni Luh Purnamasuari Prapnuwanti; I Ketut Pasek Gunawan (Universitas Negeri Yogyakarta, 2026)
Higher education institutions are places of social interaction particularly friendships where solidarity, tolerance, trust, and responsibility flourish. Every social relationship naturally has its own set of ethical norms that must be upheld and respected to foster a harmonious social environment, especially among friends. On the ground observations reveal a decline in social ethics within friendships at higher education institutions. According to data from the Kemendiktisaintek from 2021 to 2024, there were 310 reports of violence within higher education institutions, including sexual violence, bullying, and intolerance. Unhealthy social friendships can lead to declining academic performance, social isolation, and a loss of self-confidence. There is a need to strengthen and put into practice the values of Dharma, specifically the teaching of Satya. The teaching of Satya emphasizes the importance of honesty, truth, responsibility, and loyalty, which can be used to build and shape a noble character, thereby creating a healthy and harmonious friendship environment. This study is a qualitative study with a descriptive approach using interviews, literature review, and documentation. The study aims to identify the strategies used in implementing the Satya teachings, the challenges encountered, and the implications of applying the Satya teachings in shaping students’ social ethics